Differentiating Squamous Cell Carcinoma of the Cervix and Epithelioid Trophoblastic Tumor. Issue 5 (1st July 2011) - Jordan, Sara; Randall, Leslie M.; Karamurzin, Yevgeniy; Ward, Pamela; Lin, Fritz; Brewster, Wendy; Monk, Bradley J.
Abstract : Background: Epithelioid trophoblastic tumor (ETT) is a recently described subtype of gestational trophoblastic neoplasia (GTN). Its diagnosis requires a high level of suspicion because it is often mistaken for more common cervical or uterine corpus epithelial neoplasms. Case: This is a 39-year-old woman who presented with a cervical mass and positive human chorionic gonadotropin and was diagnosed with both locally advanced squamous cell cervical carcinoma and nonmetastatic GTN. She was treated unsuccessfully with concurrent intravenous cisplatin plus pelvic radiation and single-agent intravenous methotrexate. A retrospective review of the cervical biopsy using immunohistochemistry as well as genotyping of the tumor changed the original diagnosis to ETT. It is known that ETT is relatively unresponsive to chemotherapy compared with most other types of GTN; therefore, surgery would have been the optimal treatment. She died despite multiple salvage chemotherapies. Conclusions: Malignant GTN is one of the most curable gynecologic malignancies; however, its correct diagnosis is critical for the appropriate treatment. It can be easily misdiagnosed as a carcinoma because of their morphologic similarity. Genetic fingerprinting and immunohistochemistry are potentially valuable tools to confirm the diagnosis of ETT.